Rethinking the God of the Gaps Argument: An Islamic Philosophical Critique of New Atheism - Muslih, Mohammad Kholid; Miqdad Hamid al Anshory; Aldy Pradhana (Jurnal Theologia, 2025)
The persistent claim by New Atheists that belief in God merely functions as a placeholder for ignorance—commonly referred to as the "God of the Gaps" (GOG) argument—has significantly influenced contemporary discourse on the relationship between science and religion. This view asserts that the more science progresses, the less necessary God becomes, thereby reducing divine agency to an explanatory tool for unresolved phenomena. This article aims to critically examine the logic and epistemological assumptions behind the GOG argument, especially as articulated by figures such as Richard Dawkins and Christopher Hitchens. Employing a qualitative method through critical literature analysis, this study draws on primary texts from New Atheist thinkers and philosophical responses from both Western and Islamic traditions. The analysis incorporates logical critique, especially identifying fallacies such as appeal to ignorance, false dichotomy, and strawman argumentation, and integrates Islamic epistemology, particularly the distinction between rational-metaphysical knowledge (‘ilm al-ma'rifah) and empirical knowledge (‘ilm al-ma'lūmāt). The findings reveal that the GOG argument relies on a reductionist worldview that fails to account for the metaphysical dimensions of reality. As a contribution, the paper offers an Islamic philosophical framework that transcends the false dichotomy between science and religion, proposing a coherent epistemology rooted in tawḥīd that sees science as a means to understand—not replace—divine order.